Legal and Spatial Impacts of Land Conversion in Karanganyar: An Analysis of Regional Regulation 19/2019 - Novita, N; Isman, I (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The objective of this research is to ascertain whether Local Regulation No. 19/2019 has sufficiently addressed the economic, social and environmental impacts that have the potential to give rise to regulatory inconsistency. The objective of this research is to analyse the economic, social and environmental impacts of land use change policies in Karanganyar Regency in accordance with Local Regulation No. 19/2019. the research methodology employed is descriptive legal geography. The findings are presented in the following section. The land conversion policy set out in Local Regulation No. 19/2019 in Karanganyar Regency has been designed with the intention of considering the full range of economic, social and environmental impacts. However, this policy may give rise to conflicts with other policies if the regulations on community participation and alternative site design are not addressed in a more holistic manner. In practice, this results in the exclusion of environmental impact analysis from the decision-making process, thereby enabling the conversion of agricultural land into tourist sites without sufficient consideration of the potential consequences. This approach creates an imbalance and may ultimately result in unsustainability. The findings of this research can be used to enhance land use change policies in Karanganyar, facilitate local development, and provide a foundation for further research. This research is notable for its use of a legal geography approach and its focus on the Karanganyar Regency.